FIRST EXPERIENCE OF USING A CUSTOM-MADE ACETABULAR IMPLANT WITH A ZINC-CONTAINING BIOCOATING IN CLINICAL PRACTICE FOR THE TREATMENT OF DEEP PERIPROSTHETIC SURGICAL SITE INFECTIONS - Irina А. Kirilova; Peter M. Larionov; Maxim V. Efimenko; Evgeniya A. Anastasieva; Vyacheslav A. Bazlov; Maxim V. Zelikman; Alexander A. Pronskikh; Mariya B. Sedelnikova; Tatiana V. Tolkacheva; Yuri P. Sharkeev; Vitaly V. Pavlov; Andrey A. Korytkin (N.N. Priorov Journal of Traumatology and Orthopedics, 2026)
Currently, periprosthetic joint infection (PJI) of the hip joint is one of the leading causes of revision hip arthroplasty. Our study focused on the clinical manifestations of acute infection caused by Staphylococcus/Klebsiella pneumoniae using a prototype prosthesis (acetabular component) with a zinc-containing calcium phosphate coating applied by microarc oxidation as a spacer under these conditions. The study revealed that the implant with the zinc-containing calcium phosphate coating does not have a bactericidal effect in acute PJI, as there is no diffusion of zinc ions into the surrounding tissues, or the diffusion is very weak and does not provide sufficient zinc to the surrounding tissues. However, the coating under study may be effective as a preventative measure in compromised patients.